Bava’s Gift: Awakening to the Impossible by Michael Urheber - Ginsberg, Robert (Journal of Scientific Exploration, 2014)
I must admit that I had some reservations about reading this book, as all I was told was that it chronicled the author’s signs received from a discarnate friend. The prospect of wading through yet another book about pennies sent from deceased loved ones seemed onerous and a task to which I did not look forward. Not that I am averse to such manifestations and after-death communication, quite the contrary. I just prefer the evidence to be more convincing. Finding a coin that has become so devalued in our currency that half the people who drop them no longer bother to pick them up doesn’t do it for me. However, to my great delight, Michael’s message is no more about the signs than calligraphy is about the paper. The death of a loved one is often a trigger for exploration and a search for meaning, and it certainly was for the author. Following the death of a close friend, he was witness to an unfolding symphony of communications, first dismissed as coincidences, but eventually embraced and treasured in an awakened consciousness. In this case, a journey began as the result of the appearance of a simple marble that was owned by the deceased. After Michael’s friend Frank had passed, he decided to engage in an experiment by placing the marble with Frank in his coffin, specifically in his suit pocket. His initial motivation was simply to return the treasured item to its owner, but in the recesses of his mind Michael also contemplated a possible confirmation from his friend that he still survived in some fashion. He wrapped the marble in the paper on which Frank’s eulogy was written, and on the top of the paper wrote “If you are ever around, toss this back.”